Psychoneuroimmunology in the time of COVID-19: Why neuro-immune interactions matter for mental and physical health. (July 2022) - Bower, Julienne E.; Radin, Arielle; Kuhlman, Kate R.
Abstract: The brain and immune system are intricately connected, and perturbations in one system have direct effects on the other. This review focuses on these dynamic psychoneuroimmune interactions and their implications for mental and physical health in the context of the COVID-19 pandemic. In particular, we describe how psychological states influence antiviral immunity and the vaccine response, and how immune changes triggered by COVID (either via infection with SARS-CoV-2 or associated stressors) can influence the brain with effects on cognition, emotion, and behavior. We consider negative psychological states, which have been the primary focus of psychological research in the context of COVID-19 (and psychoneuroimmunology more generally). We also consider positive psychological states, including positive affect and eudaimonic well-being, given increasing evidence for their importance as modulators of immunity. We finish with a discussion of interventions that may be effective in improving immune function, the neuro-immune axis, and ultimately, mental and physical health. Highlights: There are dynamic bi-directional interactions between the brain and immune system. Both negative and positive psychological states influence antiviral immunity. Immune activation leads to behavioral changes relevant for long-haul COVID. Psychosocial interventions can enhance both mental health and immune function.